EFEKTIVITAS BIOCHAR TERHADAP KETERSEDIAAN UNSUR HARA MIKRO PADA ULTISOL - Oksana, Oksana; Taslapratama, Irwan; Novia, Muhammad Ali; Mahmud, Yusmar; Septirosya, Tiara; Shofiah, Raudhatu (Jurnal Agroteknologi, 2024)
Biochar with a high organic matter composition is considered to be an ameliorant for Ultisol. Providing biochar as an ameliorant needs to be studied because it will cause an increase in micronutrients, most of which are excessive in Ultisol. This study aims to determine the effect of several levels of biochar dosage from corn cob as a base material on changes in micronutrients in Ultisol soil. This research was conducted in a greenhouse and in the Laboratory of Agrostology, Feed Industry and Soil Science, State Islamic University of Sultan Syarif Kasim Riau. Experiments with several doses of biochar as treatment, e.g., 0%, 5%, 10%, and 15% of the composition of the growing media were arranged in a Completely Randomized Design (CRD) with six replications. The parameters observed were the micronutrient content of Boron (B), Copper (Cu), Zinc (Zn), Iron (Fe) and Aluminum (Al). The experimental results showed that giving corn cob biochar with doses of 0.5%, 10% and 15% did not significantly change the levels of B, Cu and Zn Ultisol. Biochar at a dose of 10% significantly increased the soil Zn content and decreased Al-dd Ultisol solubility.